Penerapan Desain Repacking dan Digital Marketing Rengginang Singkong Kelompok Wanita Tani Rukun Makaryo Desa Kedungdowo - Krisdiyanto Pujoningrum; Eka Risky Widyawati; Muhammad Edward Putra Armiawan; Aflit Nuryulia Praswati (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Rengginang cassava MSMEs still have many weaknesses in carrying out business activities. Weaknesses that are owned raise problems that need to be resolved. The problem being faced is a lack of knowledge about the importance of packaging design and product marketing. Food products that are traded do not use packaging designs. In addition, they only use relatively thin white plastic for product packaging. Meanwhile, good packaging with an attractive design is important to protect the product and introduce the brand to consumers. In carrying out business activities, MSMEs sell their products only in traditional markets and on the stalls of local residents. Therefore, the general public does not know of the existence of these products. The method in this service is through in-depth interviews with MSMEs actors to identify problems and solutions needed. The purpose of this activity is to provide understanding to MSMEs about the important role of packaging design and product marketing. The result of this dedication is a packaging design that can be used for MSMEs' products. MSMEs' products and locations are listed on Google Maps so that they can be accessed by the wider community. In addition, the formation of a potential map could provide information on the existence of MSMEs for road users and village migrants. It is hoped that this activity will provide material for the village government to develop community business activities.